2016
DOI: 10.1002/mame.201600035
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Polymer‐Ag Honeycomb Hybrid Film by Metal Complexation Induced Phase Separation at the Air/Water Interface

Abstract: A new facile approach for the fabrication of polymer-Ag honeycomb film is reported. A polymer-Ag + honeycomb thin film is obtained by casting a CHCl 3 solution of a functional graft copolymer on aqueous silver nitrate solution, leading to metal complexation induced phase separation at the air/ water interface. The film is reduced by UV irradiation to give a polymer-Ag honeycomb film with regular morphology. Pyrolysis of the film gives a translucent Ag honeycomb film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Functionalized graft copolymers poly(NVK‐ co ‐MAH)‐ g ‐(NH‐(PPO x ‐ co ‐PEO y )) were synthesized by graft‐onto reaction of amine‐terminated polyether [H 2 N‐[PPO x ‐ co ‐PEO y ): P1, x = 10 and y = 31; P2, x = 3 and y = 19; P3, x = 9 and y = 1] with poly(NVK‐ co ‐MAH) in the same manner with the previous report ( Scheme ) . Conductive polymer@Ag hollow core/shell nanospherical particles were synthesized from the functionalized graft copolymers and CF 3 COOAg as the silver source.…”
Section: Resultsmentioning
confidence: 96%
“…Functionalized graft copolymers poly(NVK‐ co ‐MAH)‐ g ‐(NH‐(PPO x ‐ co ‐PEO y )) were synthesized by graft‐onto reaction of amine‐terminated polyether [H 2 N‐[PPO x ‐ co ‐PEO y ): P1, x = 10 and y = 31; P2, x = 3 and y = 19; P3, x = 9 and y = 1] with poly(NVK‐ co ‐MAH) in the same manner with the previous report ( Scheme ) . Conductive polymer@Ag hollow core/shell nanospherical particles were synthesized from the functionalized graft copolymers and CF 3 COOAg as the silver source.…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, the addition of metal salt into a substrate also affects the morphology of films. Sajjad developed an approach to preparing a polymer-Ag honeycomb film by casting a polymer solution on an aqueous silver nitrate solution [33]. They found that the metal-complexation-induced phase separation approach allowed the formation of a well-defined honeycomb film.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the wastewater decontamination processes are progressing with the advancement occurring in nanomaterials such as nanoadsorbent, nano photocatalysts and some imprinted polymers. Moreover, we have recently developed range of hybrid nanomaterials based on polymers-metal complexes, which have potential applications in water treatment and pollutant removal [10,115,[154][155][156][157][158][159][160]219]. In brief, the investigation on using nanomaterial in water treatment is regarded to measure positive viewpoint [23,160,221].…”
Section: Introductionmentioning
confidence: 99%